EFFECTS OF INCLUSION OF AERIEL DRIED PARTS OF SOME HERBS IN BROILER DIETS - Yasar; S.; D. Namik; G. Fatih; A. Gokcimen; K. Selcuk (Journal of Animal and Plant Sciences, 2011)
This study determines possible antibacterial, antioxidant and growth-promoting effects of some selected herbs in broiler chickens. Ground aerial parts of Thymbra spicata, Origanum minutiflorum, Rosmarinus officinalis, Mrytus communis, Salvia tomentosa and ground seed of Cumin were added to broiler diets at 0.0, 0.25, 0.50, 1.00 and 1.50% (w/w). Volatile essential oil contents were analysed. Samples of blood, digesta and intestinal tissues were analysed to determine antioxidant activity, bacteria growth and intestinal histomorphology, respectively. The results showed that at 0-21 days of age the birds performed better on the diets up to 0.25% of herbal inclusion level. Increasing the inclusion level from 0.5 to 1.5% for Origanum minutiflorum, Thymbra spicata and partially for Rosmarinus officinalis increased feed consumption with lower weight gain and depressed efficiency of feed conversion, but not for Salvia tomentosa, Mrytus communis and Cumin. The results further showed that broilers could better perform on the diets up to 0.5% of inclusion level at 42 days. All levels (except 1.5%) for Cumin and Salvia tomentosa did not cause any impairment in performance of broilers. High inclusion levels (0.5 to 1.5%) reduced E. coli count. The selected herbs did not cause an oxidative stress at a given inclusion level. Of the plants Rosmarinus officinalis clearly demonstrated strong antioxidant effect. The high doses of Origanum minutiflorum caused depression in growth rate associated with shortened villus development of intestinal epithelium in broilers. However, increased growth rate with Cumin associated with longer villus and increased dry matter retention in broilers at 21 days were recorded. It was suggested that some of selected herbs can be incorporated up to 0.5% into broiler diets on account of their antibacterial and antioxidant properties.
Keywords: Herbs; broiler chicken; growth rate; antibacterial effect; antioxidant capacity; intestinal histomorphology.